2013
DOI: 10.1016/j.chemosphere.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Fractal structures of single-walled carbon nanotubes in biologically relevant conditions: Role of chirality vs. media conditions

Abstract: Aggregate structure of covalently functionalized chiral specific semiconducting single-walled carbon nanotubes (SWNTs) was systematically studied employing static light scattering (SLS). Fractal dimensions (Df) of two specific chirality SWNTs—SG65 and SG76 with (6, 5) and (7, 6) chiral enrichments—were measured under four biological exposure media conditions, namely: Dulbecco’s Modified Eagle Medium (DMEM), Minimum Essential Medium (MEM), Roswell Park Memorial Institute (RPMI) 1640 medium, and 0.9% saline solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…Modeling and experimental work also predict limited mobility of SWNTs in porous media due to homo-and heteroaggregation and sediments as the major long-term sink for SWNTs. [11][12][13][14][15][16] Several studies have reported little-to-no uptake of SWNTs into tissues of benthic organisms 4,8,17,18 or fish 19 exposed to SWNT amended sediments over short exposure periods up to one month, however bioaccumulation studies have not been performed under realistic, field-mimetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling and experimental work also predict limited mobility of SWNTs in porous media due to homo-and heteroaggregation and sediments as the major long-term sink for SWNTs. [11][12][13][14][15][16] Several studies have reported little-to-no uptake of SWNTs into tissues of benthic organisms 4,8,17,18 or fish 19 exposed to SWNT amended sediments over short exposure periods up to one month, however bioaccumulation studies have not been performed under realistic, field-mimetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The nitric acid treated SWCNTs post-processed with urea resulted in aggregates that are more monodisperse and rod-like in morphology (fractal dimension closer to unity) compared with the more polydisperse plate-like aggregates of acid treated only SWCNTs (fractal dimension closer to 2). [28][29][30] This enhanced dispersion is confirmed through zeta potential measurements of the different SWCNT dispersions; the magnitude of the zeta potential of SWCNTs treated for longer times and with urea is greater, underlining increased electrostatic stability. 31 While all of the chemical treatment methods enhance the extent of SWCNT dispersion, those treatment conditions resulting in equivalent or better dispersion compared to surfactant modified SWCNTs are identified and discussed as promising alternatives to the conventional surfactant methods.…”
Section: Introductionmentioning
confidence: 71%
“…(3) 28,30,44,46 As such, D f is determined from the slope of the best fit line to the log-log plot of the scattered light intensity (I) versus the scattering angle (q), calculated from Equation 3 and shown in Figure S4a-b. 28,30,44 Several studies have used SLS to evaluate the dispersed aggregate morphology of carbon nanotubes as either sphere-(D f = 3), plate-(D f = 2), or rod-(D f = 1) like.…”
Section: Evaluating the Influence Of Acid Treatment Time On Swcnt Aggmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that these D f values are indicative of the starting cluster sphericity and are likely to differ significantly as aggregation progressed over time and under different ionic conditions. 43 The noted asphericity of these clusters thus has also contributed to the deviation of the DLVO model—a model that is derived for sphere−sphere interaction.…”
Section: Resultsmentioning
confidence: 99%